LAPORAN PRAKTIK INVESTASI DI CABANG BARU MARTABAK MINI KAJEK DI JALAN KALIURANG - Bea Headystya Wildan Taufiq; Dessy Isfianadewi; Anas Hidayat (Jurnal Indonesia Sosial Teknologi, 2025)
The research method used in this business practice report is descriptive qualitative with a case study approach at the Martabak Mini Kajek business branch on Jalan Kaliurang. Data were collected through direct observation at the outlet, interviews with the owner, employees, and consumers, documentation in the form of sales records and promotional media, and literature studies related to MSME business strategies. All data were analyzed descriptively analytically by comparing the actual conditions of the business with business management theory, and using SWOT analysis and Porter's Five Forces to identify the strengths, weaknesses, opportunities, threats, and competitive position of Martabak Mini Kajek in the local culinary market.